PERBAIKAN KUALITAS CITRA SINAR X TULANG BELAKANG PENDERITA SKOLIOSIS DENGAN MENGGUNAKAN GAUSSIAN CROPPING - Sugianto, Samuel; Rasmana, Susijanto Tri; Wibowo, Madha Christian (Journal JCONES, 2013)
This paper  is to perform image enhancement to the spinal x-ray image of people with scoliosis, so that the segmentation process can be done better. Image filtered with Modified Tophat filter were cropped using a vertical windowed Gaussian function with manually initialized center of peak points trough the spinal feature, thus the pixels on the both side of the center of peak points will gradually decrease, leaving only the spinal part. By using this Gaussian cropping, the success rate in segmentation process would increase.